A Retrospective Analysis of Portuguese Elite Athletes' Involvement in International Competitions - Barreiros, A. N.; Fonseca, A. M. (International Journal of Sports Science and Coaching, 2012)
The primary purpose of the present study was to determine how many international senior athletes competed at the international level during their development. This examination was conducted across different sports, genders, and levels of success. 532 international senior athletes of four Olympic sports (soccer, Volleyball, swimming, and Judo) who were born between 1974 and 1983 and competed at National squads between 1988 and 2008. The results showed, particularly at team sports, that a significant number of athletes did not have any international experience during their development äs a youth. Overall, results suggest that early involvement in international events and selection of talent during early ages is not a pre-requisite of success, particularly in team and male sports.